2016
DOI: 10.11622/smedj.2016007
|View full text |Cite
|
Sign up to set email alerts
|

Underdiagnosis of delirium on admission and prediction of patients who will develop delirium during their inpatient stay: a pilot study

Abstract: , MBChB, FRCP INTRODUCTION The study aimed to determine the prevalence and documentation of delirium among the elderly and if the Clock Drawing Test (CDT) can be used to predict which patients had delirium on admission and those who may develop delirium during their stay in acute medical wards. METHODSA single researcher performed the Mini-Mental State Examination (MMSE) and CDT on admission and discharge of 57 elderly adults at the National University Hospital, Singapore. Delirium was defined as a ≥ 3-poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
4
20
0
2
Order By: Relevance
“…Prevalence of delirium detected by CAM in the present study was 28.2%, which is similar to the prevalence of 28.1% reported by a recent study with patients aged 60 years or more treated in an emergency service . It is also in agreement with the literature, which shows a prevalence of delirium ranging from 10% to 30% in elderly individuals admitted through the emergency department .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Prevalence of delirium detected by CAM in the present study was 28.2%, which is similar to the prevalence of 28.1% reported by a recent study with patients aged 60 years or more treated in an emergency service . It is also in agreement with the literature, which shows a prevalence of delirium ranging from 10% to 30% in elderly individuals admitted through the emergency department .…”
Section: Discussionsupporting
confidence: 91%
“…Despite the high prevalence of delirium in the sample, the physicians in the present study did not consider this possibility in 64.5% of patients. This translated to low diagnostic sensitivity (35.5%) and accuracy (81.8%), but excellent specificity (100%), a fact that has also been reported in a recent study . Another study carried out with the elderly in an emergency department reported a sensitivity of 45% and a specificity of 97% for the diagnosis of delirium, which is similar to what we observed .…”
Section: Discussionsupporting
confidence: 90%
“…A prevalência de delirium neste estudo foi de 25,6%, condizente com a literatura. 5,7,19,20,22,23 Até onde sabemos, o AMT é o primeiro teste adaptado para a população brasileira para avaliação de delirium em unidades de urgência que pode ser aplicado diretamente ao paciente, sem a necessidade de um informante. Além de sua aplicação durar menos de 1 minuto, 18 o fato de o AMT não depender de um informante, que muitas vezes não está disponível na primeira avaliação do idoso, permite uma avaliação rápida do estado cognitivo em serviços de urgência, o que pode reduzir de fato o tempo de diagnóstico de delirium.…”
Section: Discussionunclassified
“…In other words, given that this is a survivor cohort, patients need to survive until a formal dementia diagnosis is established. Another shortcoming relates to the rate of clinical diagnosis of DLB and delirium which is often cited as being under reported in the hospital setting 3,33,34 . Further, some patients might have protracted episodes of delirium 15 , lasting longer than the two weeks used in this analysis to distinguish separate episodes in this analysis.…”
Section: Limitations Of the Studymentioning
confidence: 99%